Effects of Soaking Followed by Hydrothermal Processing on Proximate Composition and Mineral Elements of Cassia hirsutta: An Underutilised Hard-to-Cook Legume - Ojo, Moses Ayodele; Ade-Omowaye, Beatrice I.O.; Ade-Omowaye, Beatrice I.O. (Pakistan Journal of Nutrition, 2019)
Background and Objective: Cassia hirsutta is an underutilised hard-to-cook legume in South-West Nigeria. This study was designed to investigate the effects of soaking prior to application of four hydrothermal techniques on the nutrient contents of Cassia hirsutta. Materials and Methods: Four hydrothermal processing techniques (atmospheric boiling, atmospheric steaming, pressure boiling and pressure steaming) were used to process the seeds of Cassia hirsutta after aqueous soaking at varying hydration levels. Results: Soaking of the seeds prior to hydrothermal processing caused reduction in cooking time. The hydrothermal techniques had significant (p<0.05) effects on the nutrients. Maximum reduction of 58.86% in cooking time was effected when the seeds were hydrated to 100% followed by boiling at elevated pressure. The protein content was better conserved when seeds were processed at elevated pressure. Legume samples cooked at 100% hydration levels have better retention of mineral elements. Conclusion: Although all the hydrothermal processing techniques caused varying degree of seepage, the cooked legume seed is a good source of nutritionally important nutrients. Further adaptation of this underutilised legume in human diets and feeds will alleviate the problem of food and nutrition insecurity in developing countries.